2017
DOI: 10.1016/j.yclnex.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Aronia juice suppresses the elevation of postprandial blood glucose levels in adult healthy Japanese

Abstract: of these enzyme activities and may be useful for prevention of metabolic diseases in adult healthy Japanese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Epidemiological studies indicate that anthocyanin consumption from different plant foods is associated with a reduced type 2 diabetes risk (Wedick et al, 2012). Chokeberry juice is a rich source of polyphenol compounds that could be effective preventive and therapeutic agents in DM type 2 (Banjari et al, 2017;Simeonov et al, 2002;Yamane et al, 2017). Chokeberry juice supplementation in patients with DM type 2 could have an impact on the patient's health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies indicate that anthocyanin consumption from different plant foods is associated with a reduced type 2 diabetes risk (Wedick et al, 2012). Chokeberry juice is a rich source of polyphenol compounds that could be effective preventive and therapeutic agents in DM type 2 (Banjari et al, 2017;Simeonov et al, 2002;Yamane et al, 2017). Chokeberry juice supplementation in patients with DM type 2 could have an impact on the patient's health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Aronia products (extracts, juices, supplements, etc.) are known from their beneficial impact on human health (Boncheva et al, ; Borowska & Brzóska, ; Yamane et al, ). Consumption of these products is recommended as a prophylactic for various diseases, including non‐communicable diseases such as diabetes, obesity, digestive system disorders, cardiovascular system disorders and cancer (Boncheva et al, ; Borowska & Brzóska, ; Jurikova et al, ; Yamane et al, ).…”
Section: Polyphenol‐rich Products In Protection and Treatment Of Cd‐imentioning
confidence: 99%
“…are known from their beneficial impact on human health (Boncheva et al, ; Borowska & Brzóska, ; Yamane et al, ). Consumption of these products is recommended as a prophylactic for various diseases, including non‐communicable diseases such as diabetes, obesity, digestive system disorders, cardiovascular system disorders and cancer (Boncheva et al, ; Borowska & Brzóska, ; Jurikova et al, ; Yamane et al, ). The study by Boncheva et al () has revealed that consumption of juice from chokeberries (200 mL daily for 60 days) improved liver function (estimated based on the serum activities of liver marker enzymes), carbohydrate metabolism and lipid parameters in the serum of people with NAFLD.…”
Section: Polyphenol‐rich Products In Protection and Treatment Of Cd‐imentioning
confidence: 99%
See 1 more Smart Citation
“…High anthocyanin contents in A. melanocarpa have led to investigating the bioactives present in its extracts ( 12 , 13 ). A. melanocarpa juice (200 mL) was shown to have a potent effect on postprandial glucose in healthy subjects after an oral meal tolerance test ( 14 ). This effect was imparted regardless of the gender of the subjects and was additionally shown to reduce the activity of dipeptidyl peptidase IV, α-glucosidase, and angiotensin-converting enzyme (ACE) in a dose-dependent manner ( 14 ).…”
Section: Antidiabetic Effects Of a Melanocarpamentioning
confidence: 99%